PENGARUH KINERJA KEUANGAN PERIODE SEBELUMNYA TERHADAP PROSES PERENCANAAN ANGGARAN DAN PENGENDALIAN ANGGARAN - Josua Erwin Simanjuntak; Pangaribuan, Hisar; Siagian, Harlyn (JURNAL EKBIS, 2024)
The lack of budget utilization for financial planning and control in non-profit organizations potentially leads to poor financial performance. The aim of this research is to analyze the influence of financial performance on budget planning and control processes in non-profit organizations, with the hope of providing theoretical and practical contributions to their financial management. This study employs a quantitative approach, collecting data through surveys from 16 non-profit organizations in Indonesia, using purposive sampling method. Primary data is gathered through questionnaires exploring budget planning and control processes, with responses measured using Likert scale. Data analysis is conducted using simple regression technique to evaluate the influence of financial performance on budget planning and control processes. SPSS 22 software is utilized for data analysis. The results indicate a significant positive influence between non-profit organization's financial performance and budget planning process, as well as between financial performance and budget control. This contributes significantly to understanding budget management in non-profit organizations